Towards A Sustainable City: Strategic Approach To Smart City Development (Future Cities and Environment, 2025)
The rapid development of technology and urbanization has encouraged many cities around the world to adopt the Smart City concept as a strategy to achieve sustainability. Smart City integrates information and communication technology (ICT) into urban management to improve efficiency, public services and the quality of life of its residents. This study examines various strategies to develop the Smart City concept with a focus on sustainability aspects. The approach used includes literature analysis, case studies, and interviews with experts in urban planning and technology. The main findings show that effective Smart City implementation requires a comprehensive framework that includes advanced technological infrastructure, active community participation, supportive government policies, and collaboration among stakeholders. In addition, proper and transparent data management is essential for accurate and responsive decision-making. The study also highlights the importance of environmental aspects in Smart City development, such as the use of renewable energy, efficient waste management, and environmentally friendly transportation. Conclusion, a sustainable Smart City development strategy depends not only on advanced technology but also on the synergy between technology, policy, and society. Therefore, the Smart City concept can be an effective solution to address the challenges of urbanization and achieve the goal of sustainable cities in the future.